PERAMALAN FUNGSI TRANSFER SINGLE INPUT PADA HARGA EMAS PASAR KOMODITI - Dhevi Ratna Fitriani; Moh Yamin Darsyah; Rochdi Wasono (Universitas Muhammadiyah Semarang, 2017)
The transfer function model is one of multiple time series models that combineARIMA model characteristics with one variable of regression analysis. Anincreasingly growing world of investment and many types of investments.Thevalue of gold precious metals that have never experienced depreciation. Makepeople prefer gold as a profitable investment tool. Information on gold prices isan important issue for investors. Therefore, researchers want to find a modeland predict the price of commodity gold market using the method of single inputtransfer function. The data used is the world gold data commodity market, andinflation data of 2008-2017 in units of the month. In the results of forecastingthat has been anti ln addressing the peak of price increases occurred in August2018 which reached 1481. while December 2017 is the month of the lowestgold price of 1188.06, and the forecast shows that throughout the year all themonths of rising prices while the month that only declined in price only threemonths ie in May 2017, November 2017 and December 2017. Keywords: Transfer function, Single Input, Gold Price